A taxonomic review of the family Trachipteridae (Acanthomorpha: Lampridiformes), with an emphasis on taxa distributed in the western Pacific Ocean - Martin, Jennifer M.; Hilton, Eric J. (Zootaxa, 2021)
The family Trachipteridae—the Ribbonfishes, Dealfishes, and their relatives—has a circumglobal distribution, with at least 10 species in three genera (Zu Walters & Fitch 1960, Desmodema Walters & Fitch 1960, and Trachipterus Goüan 1770) that are characterized by elongate, extremely laterally compressed bodies, large eyes, absence of ribs, spines on lateral-line scales, greatly protrusible mouths, and a lack of pelvic fins in adults. They are also known for the drastic morphological changes that occur during ontogeny. Trachipterids are poorly represented in collections due to the fragile nature of their bodies. Most studies of the Trachipteridae have been limited by the numbers, developmental stages, and the completeness of the specimens that were examined. Along with the lack of available material, incomplete and conflicting character information compounds the taxonomic confusion of Trachipteridae. Despite the body of regional revisions that have examined trachipterid taxonomy, none have synthesized a suite of morphological characters across ontogeny. The goals of this paper are to (1) revise the family Trachipteridae, (2) revise the genera Trachipterus, Zu, and Desmodema, including information regarding ontogeny and biogeography, and 3) address the alpha taxonomy of Zu, Desmodema, and Trachipterus from the western Pacific Ocean. We recognize possibly five species of Trachipterus as being present in the western Pacific, as well as two species of both Zu and Desmodema. Despite additions to the specimen base that allows refinement of taxonomy and diagnoses, there are still large knowledge gaps associated with the taxonomic review of Trachipteridae. These reflect incomplete understanding of geographic distribution of taxa which may mask unrecognized taxonomic variability. The genus Trachipterus specifically remains problematic and will require greater detailed global study. Early life history stages remain unknown for several taxa which hinders full interpretation of ontogenetic transitions. Protracted transitions, some of which are clarified here, further confuse stage-based diagnoses and must be considered in future analyses of this family.